Composite nanofiltration membrane with high flux and high chemical resistance as well as preparation method and application of composite nanofiltration membrane

By forming an intermediate layer on the porous support layer of the polyethersulfone in the nanofiltration membrane, the reaction of macrocyclic polyamine and epoxy modified silicone resin emulsion is used to regulate the polyamide layer structure, which solves the problem that existing nanofiltration membranes are difficult to ensure high flux and high chemical resistance at the same time, and achieves efficient water flux and chemical resistance.

CN119565397AActive Publication Date: 2025-03-07WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746407.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

While improving the water transport path and adjusting the interface polymerization process, existing nanofiltration membranes can easily affect the stability of the polyamide layer or lead to performance losses, making it difficult to ensure high throughput and high chemical resistance at the same time.

Method used

By forming an intermediate layer on the polyethersulfone porous support layer, the polyamide layer structure is regulated by the reaction of macrocyclic polyamine and epoxy modified silicone resin emulsion, and a separation layer is formed through interfacial polymerization, thereby improving the water flux and chemical resistance of the film.

Benefits of technology

The high flux and high chemical resistance of the nanofiltration membrane are achieved, which improves water flux and enhances resistance to chemical attacks, ensuring the stability and performance of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163840440000061
    Figure BDA0005163840440000061
Patent Text Reader

Abstract

The invention provides a high-flux and high-chemical-resistance composite nanofiltration membrane as well as a preparation method and application thereof. The nanofiltration membrane comprises a polyethersulfone porous support layer, a middle layer formed by reaction of macrocyclic polyamine and epoxy modified organic silicon resin emulsion, and a polyamide separation layer formed on the middle layer. Wherein the middle layer is formed by loading macrocyclic polyamine and epoxy modified organic silicon resin emulsion on the polyethersulfone porous supporting layer and carrying out heat treatment reaction and curing reaction, and the separation layer is prepared by carrying out interfacial polymerization reaction on a water phase containing polyamine and an organic phase containing polyacyl chloride. The intermediate layer provides reaction sites, regulates and controls a polyamide separation layer structure, constructs an effective water channel, effectively improves the membrane flux, and active sites of the intermediate layer can prevent polyamide from direct chemical attack, so that the chemical resistance of the membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment membranes, and in particular relates to a high-flux and high-chemical-resistance composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] In recent years, membrane technology has played an increasingly important role in gas separation, aqueous solution separation, separation and purification of chemical products and biochemical products, and has been widely used in food and beverage processing, industrial wastewater treatment, large-scale gas separation, hydrometallurgical technology and other fields. Nanofiltration membrane is an important branch of membrane technology, with a molecular weight cutoff between 200-2000 and a multi-charged surface. Under the combined action of multiple mechanisms such as pore size screening and Donan effect, nanofiltration membrane has a selective separation effect on monovalent and multivalent salt ions, and has different interception effects on organic matter of different molecular weights. It has been widely used in chlor-alkali denitrification, lithium extraction from salt lakes, municipal water treatment, concentration and purification of pharmaceutical active substances, and seawater desalination pretreatment.

[0003] The introduction of an intermediate layer between the nanofiltration membrane base film and the polyamide retention layer can optimize the water transport path of the nanofiltration membrane, thereby improving the overall water permeability of the membrane. In addition, the rich active sites on the intermediate layer can also regulate the interfacial polymerization process, thereby affecting the properties of the polyamide retention layer. However, the introduction of many intermediate layers will affect the stability of the polyamide layer or cause other performance losses.

[0004] Based on the current research on the intermediate layer of nanofiltration membrane, it is necessary to propose a new method of using the intermediate layer to regulate membrane performance based on the composite nanofiltration membrane prepared by the traditional interfacial polymerization method, so as to improve the flux and high chemical resistance of the composite nanofiltration membrane while ensuring the separation characteristics of the nanofiltration membrane. Summary of the invention

[0005] One of the purposes of the present invention is to provide a high-flux, high-chemical-resistance nanofiltration membrane, which regulates the structure of the polyamide layer through an intermediate layer, thereby increasing the water flux of the membrane and providing attack sites for chemical attack through the intermediate layer, thereby avoiding direct attack of polyamide on the amide bonds and improving the chemical resistance of the membrane.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0007] In a first aspect, the present invention provides a high-flux and high-chemical-resistance composite nanofiltration membrane, which comprises a polyethersulfone porous support layer, an intermediate layer formed by the reaction of macrocyclic polyamine and epoxy-modified silicone resin emulsion, and a polyamide separation layer formed on the intermediate layer.

[0008] The second aspect of the present invention provides a method for preparing a high-flux and high-chemical-resistant composite nanofiltration membrane.

[0009] A method for preparing the above-mentioned high-flux and high-chemical-resistant composite nanofiltration membrane, the method comprising the following steps:

[0010] (1) loading a macrocyclic polyamine and an epoxy-modified silicone resin emulsion on a polyethersulfone porous support layer to form an intermediate layer;

[0011] (2) The aqueous phase containing the polyamine and the organic phase containing the polyacid chloride form a separation layer on the intermediate layer through interfacial polymerization.

[0012] In one embodiment of the present invention, step (1) specifically comprises: immersing the polyethersulfone porous support layer in a macrocyclic polyamine solution and an epoxy-modified silicone resin emulsion in sequence, draining, and removing excess liquid on the surface.

[0013] Preferably, the macrocyclic polyamine is selected from one or more of 1,5,9,13-tetraazacyclohexadecane, 1,5,8,11,14-pentaazacyclohexadecane, 1,4,8,11-tetraazacyclotetradecane, 1,4,7,10-tetraazacyclododecane, and 1,5,9-triazacyclododecane; the solvent of the macrocyclic polyamine solution can be water or an organic solvent (such as methanol), which is not limited. The concentration of the macrocyclic polyamine solution is 2 to 10 wt%, such as 3 wt%, 5 wt%, 6 wt%, and 8 wt%;

[0014] Preferably, the epoxy value of the epoxy-modified silicone resin emulsion is 0.1-0.3, and the solid content is preferably 40-60%.

[0015] Preferably, the immersion time of the polyethersulfone porous support layer in the macrocyclic polyamine solution is 2 to 10 minutes; and the immersion time in the epoxy-modified silicone resin emulsion is 10 to 60 minutes.

[0016] In one embodiment of the present invention, the polyamine in step (2) is an aliphatic polyamine, and the polyacyl chloride is an aromatic polyacyl chloride; step (2) specifically comprises: mixing the aliphatic polyamine with water to obtain an aqueous phase solution, mixing the aromatic polyacyl chloride with an organic solvent to obtain an oil phase solution, contacting the polyethersulfone porous supporting layer supporting the intermediate layer with the aqueous phase solution, removing excess surface solution, contacting with the oil phase solution, heating and curing the intermediate layer, and further polymerizing the separation layer to obtain the nanofiltration membrane.

[0017] In one embodiment of the present invention, the aliphatic polyamine is selected from one or more of piperazine, ethylenediamine, triethylenetetramine, tetraethylenepentamine and aminoethylpiperazine; preferably, the concentration of the aqueous solution of the aliphatic polyamine is 1-2.5 wt%.

[0018] In one embodiment of the present invention, the aromatic polyacid chloride is selected from one or more of trimesoyl chloride, phthaloyl chloride and isophthaloyl chloride.

[0019] In one embodiment of the present invention, the organic solvent in the oil phase solution is selected from one or more of n-hexane, n-heptane, n-decane, Isopar L and Isopar G isomeric alkanes; preferably, the concentration of the oil phase solution is 0.1-0.25 wt%.

[0020] In one embodiment of the present invention, the polyethersulfone porous supporting layer supporting the intermediate layer is in contact with the aqueous solution for 2 to 10 minutes, and is in contact with the oily solution for 1 to 3 minutes.

[0021] In one embodiment of the present invention, after contacting with the oil phase solution, the surface solution is removed and then heat curing is performed. The heating curing temperature is 100 to 180° C. and the time is 2 to 20 minutes.

[0022] The third aspect of the present invention provides a use of a composite nanofiltration membrane.

[0023] A use of a composite nanofiltration membrane, wherein the nanofiltration membrane is the above-mentioned nanofiltration membrane, or is a nanofiltration membrane prepared by the above-mentioned method, and the nanofiltration membrane is used as a high-flux and high-chemical-resistant nanofiltration membrane, preferably a nanofiltration membrane used in water treatment and material separation components.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] In the preparation method of the present invention, macrocyclic polyamine and epoxy-modified silicone resin emulsion are firmly loaded on the polyethersulfone porous support layer through the reaction of amino and epoxy and subsequent heat treatment curing, so as to form an intermediate layer to regulate the morphology of the poly-nanofiltration membrane and increase the surface undulation of the polyamide separation layer. At the same time, the intermediate layer provides reaction sites, and the unreacted amino part of the macrocyclic polyamine reacts with the acyl chloride, and the epoxy group of the epoxy silicone resin can react with the carboxyl group after the hydrolysis of the acyl chloride, which can directly affect the polyamide network structure, construct water channels, improve the water flux of the membrane, and improve the bonding stability of the support layer and the intermediate separation layer. At the same time, it can reduce the direct attack of chemicals such as oxidants and sodium hydroxide on the surface of the nanofiltration membrane to a certain extent, and improve its chemical resistance. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0027] The separation performance of the prepared nanofiltration membrane is mainly evaluated by two characteristic parameters, namely the water flux and retention rate of the membrane.

[0028] Water flux (LMH) is defined as the volume of water that passes through the effective membrane area per unit time under certain operating pressure conditions.

[0029] Retention rate calculation formula: R = (1 – TOCp / TOC f )×100%, where R represents the interception rate, TOC p and TOC f are the concentrations of total organic carbon (TOC) in the permeate and feed liquid (ppm), respectively.

[0030] Total organic carbon (TOC) was determined using a multi N / C 2100TOC total organic carbon / total nitrogen analyzer from Jena, Germany.

[0031] The separation performance of the membrane was determined by cross-flow test using the Huzhou Yuequan nanofiltration membrane test bench.

[0032] The test conditions for the separation performance of the membrane of the present invention are: the feed liquid is a 100 ppm sucrose solution, the feed liquid temperature is 25° C., and the operating pressure is 0.69 MPa (gauge pressure).

[0033] In order to better understand this test method, the steps are briefly described as follows.

[0034] (1) Solution preparation: Prepare a 100 ppm sucrose aqueous solution as the initial performance test stock solution.

[0035] (2) Initial performance test: The membrane that has undergone the initial performance test is subjected to a cross-flow test at 0.69 MPa, and the test raw liquid and permeate are taken to test TOC.

[0036] (3) Chlorine resistance test: The static immersion method was used to place the membrane that had completed the separation performance test in a sodium hypochlorite aqueous solution with a pH of 7.0 and containing 1000 ppm of active chlorine. The solution was immersed in the solution at a constant temperature of 25.0±0.5°C for 24 h. The product of the active chlorine concentration and the immersion time (ppm·h) was used as the chlorination intensity index. The chlorinated membrane was then repeatedly rinsed with deionized water to completely remove the active chlorine remaining in the membrane. Finally, the changes in the membrane's sucrose retention performance were tested under the aforementioned test conditions to examine the membrane's chlorine resistance.

[0037] (4) Alkali resistance test: The membrane that has completed the separation performance test was placed in a sodium hydroxide aqueous solution with a pH of 13.0 and immersed at a constant temperature of 35.0±0.5°C for 24 h. The membrane treated with alkali solution was then repeatedly rinsed with deionized water. Finally, the change in the membrane's sucrose retention performance was tested under the aforementioned test conditions to examine the membrane's alkali resistance.

[0038] The main raw materials used in the specific implementation of the present invention are shown in Table 1.

[0039] Table 1 Main raw materials

[0040] Raw material name Parameters Manufacturer Polyethersulfone membrane Pore ​​diameter 50nm Wanhua Chemical Anhydrous piperazine Purity ≥99% Aladdin Reagent Trimesoyl chloride Purity ≥99% Sanlibenno n-Decane Purity ≥98% Aladdin Reagent Macrocyclic polyamines Purity ≥99% Merck Epoxy modified silicone resin emulsion Epoxy value 0.1-0.3, solid content 50% Shenzhen Jipeng Silicon Fluorine Materials sucrose Purity ≥99% Aladdin Reagent

[0041] Example 1

[0042] The polyethersulfone base membrane was immersed in a methanol solution of 1,4,8,11-tetraazacyclotetradecane with a concentration of 2wt% for 2 minutes, and then vertically drained to remove the liquid on the membrane surface. The base membrane was then immersed in an epoxy-modified silicone resin emulsion with an epoxy value of 0.1 for 10 minutes, and then vertically drained to remove the liquid on the membrane surface. It was immersed in an aqueous solution containing 1.5wt% piperazine for 2 minutes, and then vertically drained to remove the liquid on the membrane surface. It was then immersed in an n-decane oil phase solution containing 0.15wt% trimesoyl chloride for 1 minute. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0043] Example 2

[0044] The polyethersulfone base membrane was immersed in an aqueous solution of 1,4,7,10-tetraazacyclododecane with a concentration of 8wt% for 10 minutes, and then vertically drained to remove the liquid on the membrane surface. The base membrane was then immersed in an epoxy-modified silicone resin emulsion with an epoxy value of 0.3 for 60 minutes, and then vertically drained to remove the liquid on the membrane surface. It was immersed in an aqueous phase solution containing 2.5wt% triethylenetetramine for 10 minutes, and then vertically drained to remove the liquid on the membrane surface. It was then immersed in an n-decane oil phase solution containing 0.20wt% trimesoyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 180°C oven for reaction time of 20 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0045] Example 3

[0046] The polyethersulfone base membrane was immersed in an aqueous solution of 1,5,9-triazacyclododecane with a concentration of 5wt% for 5 minutes, and then vertically drained to remove the liquid on the membrane surface. The base membrane was then immersed in an epoxy-modified silicone resin emulsion with an epoxy value of 0.2 for 30 minutes, and then vertically drained to remove the liquid on the membrane surface. It was immersed in an aqueous phase solution containing 1.5wt% piperazine for 2 minutes, and then vertically drained to remove the liquid on the membrane surface. It was then immersed in an n-decane oil phase solution containing 0.15wt% isophthaloyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0047] Comparative Example 1

[0048] The polyethersulfone-based membrane was immersed in an aqueous solution containing 1.5 wt% piperazine for 2 minutes, then vertically drained to remove the liquid on the membrane surface, and then immersed in an n-decane oil solution containing 0.15 wt% trimesoyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0049] Comparative Example 2

[0050] The polyethersulfone-based membrane was immersed in an aqueous solution of 1,5,9-triazacyclododecane with a concentration of 5wt% for 5 minutes, and then vertically drained to remove the liquid on the membrane surface, immersed in an aqueous solution containing 1.5wt% piperazine for 2 minutes, and then vertically drained to remove the liquid on the membrane surface, and then immersed in an n-decane oil phase solution containing 0.15wt% trimesoyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0051] Comparative Example 3

[0052] The polyethersulfone-based membrane was immersed in an epoxy-modified silicone resin emulsion with an epoxy value of 0.2 for 30 minutes, then vertically drained to remove the liquid on the membrane surface, immersed in a mixed aqueous phase solution containing 1.5wt% piperazine for 2 minutes, then vertically drained to remove the liquid on the membrane surface, and then immersed in an n-decane oil phase solution containing 0.15wt% trimesoyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0053] Comparative Example 4

[0054] The polyethersulfone-based membrane was immersed in an epoxy-modified silicone resin emulsion with an epoxy value of 0.2 for 30 minutes, then vertically drained to remove the liquid on the membrane surface, immersed in a mixed aqueous solution containing 1.5wt% piperazine and 5.0wt% 1,5,9-triazacyclododecane for 2 minutes, then vertically drained to remove the liquid on the membrane surface, and then immersed in an n-decane oil phase solution containing 0.15wt% trimesoyl chloride for 2 minutes. After vertically draining to remove the liquid on the membrane surface, it was placed in a 150°C oven for reaction time of 10 minutes, taken out and immersed in deionized water to obtain a nanofiltration membrane.

[0055] Table 2 Nanofiltration membrane performance test of Examples 1 to 3 and Comparative Examples 1 to 4

[0056]

[0057] From the test results in Table 2, it can be seen that when the intermediate layer is prepared using macrocyclic polyamine and epoxy-modified silicone resin emulsion, the flux of the nanofiltration membrane at 0.69 MPa is significantly improved compared with that of Comparative Examples 1 to 4, the retention rate is greater than 90%, and the retention rate after chlorine and alkali resistance tests is stable, and the chemical resistance of the membrane is greatly improved.

[0058] In comparative examples 1 to 4, the lack of an intermediate layer of synergistic action of macrocyclic polyamine and epoxy-modified silicone resin makes it impossible to simultaneously ensure a high initial flux and retention rate of the nanofiltration membrane, and the retention rate drops significantly after chlorine or alkali resistance treatment.

Claims

1. A high-flux and high-chemical-resistance composite nanofiltration membrane, characterized in that: The nanofiltration membrane comprises a polyethersulfone porous support layer, an intermediate layer formed by the reaction of macrocyclic polyamine and epoxy-modified organic silicone resin emulsion, and a polyamide separation layer formed on the intermediate layer.

2. A method for preparing a high-throughput and high-chemical-resistant composite nanofiltration membrane, characterized in that: The following steps are involved: (1) macrocyclic polyamine and epoxy-modified silicone resin emulsion are loaded on the polyethersulfone porous support layer to form an intermediate layer; (2) The aqueous phase containing the polyamine and the organic phase containing the polyacid chloride form a separation layer on the intermediate layer through interfacial polymerization.

3. The method according to claim 2, characterized in that Step (1) specifically comprises: immersing the polyethersulfone porous support layer in a macrocyclic polyamine solution and an epoxy-modified silicone resin emulsion in sequence, draining, and removing excess solution on the surface.

4. The method according to claim 3, characterized in that The macrocyclic polyamine is selected from one or more of 1,5,9,13-tetraazacyclohexadecane, 1,5,8,11,14-pentaazacyclohexadecane, 1,4,8,11-tetraazacyclotetradecane, 1,4,7,10-tetraazacyclododecane and 1,5,9-triazacyclododecane; And / or, the concentration of the macrocyclic polyamine solution is 2 to 10 wt%.

5. The method according to claim 3 or 4, characterized in that: The immersion time of the polyethersulfone porous support layer in the macrocyclic polyamine solution is 2 to 10 minutes; And / or, the immersion time of the polyethersulfone porous support layer in the epoxy-modified silicone resin emulsion is 10 to 60 minutes.

6. The method according to claim 3, characterized in that The epoxy value of the epoxy-modified silicone resin emulsion is 0.1-0.

3.

7. The method according to claim 2, characterized in that: The polyamine in step (2) is an aliphatic polyamine, and the polyacyl chloride is an aromatic polyacyl chloride; Preferably, step (2) is specifically as follows: aliphatic polyamine is mixed with water to obtain an aqueous phase solution, aromatic polyacyl chloride and an organic solvent are mixed to obtain an oil phase solution, the polyethersulfone porous supporting layer supporting the intermediate layer is contacted with the aqueous phase solution, excess solution on the surface is removed, contacted with the oil phase solution, and heated and solidified to obtain the nanofiltration membrane.

8. The method according to claim 7, characterized in that The aliphatic polyamine is selected from one or more of piperazine, ethylenediamine, triethylenetetramine, tetraethylenepentamine and aminoethylpiperazine; Preferably, the concentration of the aqueous solution is 1 to 2.5 wt %; and / or, the aromatic polyacyl chloride is selected from one or more of trimesoyl chloride, phthaloyl chloride and isophthaloyl chloride; Preferably, the organic solvent is selected from one or more of n-hexane, n-heptane, n-decane, Isopar L and Isopar G isoparaffins; Preferably, the concentration of the oil phase solution is 0.1 to 0.25 wt %; and / or, the polyethersulfone porous support layer supporting the intermediate layer is in contact with the aqueous solution for 2 to 10 minutes; And / or, the polyethersulfone porous supporting layer carrying the intermediate layer is in contact with the oil phase solution for 1 to 3 minutes.

9. The method according to claim 7 or 8, characterized in that: The heating curing temperature is 100-180°C and the time is 2-20 minutes.

10. Use of the composite nanofiltration membrane according to claim 1 or the composite nanofiltration membrane prepared by the preparation method according to any one of claims 2 to 9, characterized in that: The nanofiltration membrane is used as a water treatment or material separation component.

Citation Information

Patent Citations

  • Dust-proof and haze-proof transparent window screen and preparation method thereof

    CN105863478A

  • Preparation method of multilayer reverse osmosis composite membrane

    CN111203105A

  • Preparation method and application of high-permeability hybrid silicon film

    CN115445449A

  • Nanofiltration membrane with silanol three-dimensional network middle layer and preparation method of nanofiltration membrane

    CN117138577A

  • Method for preparing nanofiltration membrane and nanofiltration membrane prepared therefrom

    WO2021128886A1